Vila do Mar: imagem urbana, topocepção e a noção de lugar - Garcia, Fernanda Zednik (2021)
The Vila do Mar research: urban image, topoception and the notion of place seeks evaluate the Vila do Mar project, carried out on the west coast of the city of Fortaleza, in region called Grande Pirambu, under the prism of urban image and topoception. These concepts are linked to the humanist vision of architecture, which incorporates issues such as memories, history and culture in urban design, related to the geographical and cultural concepts of place. Vila do Mar is part of one of the the poorest and most unequal regions of the city of Fortaleza, but at the same time, has a rich history of struggles for community rights, culture, heritage immaterial and a sense of belonging, which inserts it in the characteristic of place, a categories of intangible cultural heritage. The project, promoted by power public, was exposed as an attempt to leave behind a past of neglect and lack of urban infrastructure, proposing an urban space connected to the community. Also, the Vila do Mar project was carried out in a region with exuberant maritime landscape and high tourist potential, which can, at the same time, de-characterize the region and expel local residents, as well as contribute for the development of the region. Thus, this work seeks to investigate how this project was thought in terms of topoceptive and imagery aspects and, mainly, in the context of place. For this, an exhibition of the contribution of some theorists on the subject, namely Kevin Lynch, Gordon Cullen and Maria Elaine Kohlsdorf, and specific considerations regarding cultural heritage in the context of subnormal housing and informal Brazilian agglomerations.